1979
DOI: 10.1182/blood.v54.4.877.877
|View full text |Cite
|
Sign up to set email alerts
|

Serum erythropoietin concentration in chronic renal failure: relationship to degree of anemia and excretory renal function

Abstract: By use of the fetal mouse liver cell assay, serum erythropoietin (SEp) concentration was measured in 135 patients at various stages of chronic renal failure and in 59 healthy subjects. In patients with creatinine clearances (CCr) ranging from 2 to 40 ml/min/1.73 sq m, endocrine renal function was found to deteriorate in parallel to excretory renal function. The known negative correlation between SEp and hematocrit (Hct) was not apparent, probably because of the loss of renal mass accompanying progress of anemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…A significant fall in SEp with haemodialysis was also reported by Radtke et a1 (1980). As their patients also had a significant rise in haematocrit, the fall in Ep represents an appropriate physiological response to improved tissue oxygen delivery, the relationship between SEp and haema-tocrit being normally an inverse one (Radtke et al 1979). In our patients, SEp also fell but there was no change in Hb or haematocrit.…”
Section: Serum Erythropoietinsupporting
confidence: 49%
“…A significant fall in SEp with haemodialysis was also reported by Radtke et a1 (1980). As their patients also had a significant rise in haematocrit, the fall in Ep represents an appropriate physiological response to improved tissue oxygen delivery, the relationship between SEp and haema-tocrit being normally an inverse one (Radtke et al 1979). In our patients, SEp also fell but there was no change in Hb or haematocrit.…”
Section: Serum Erythropoietinsupporting
confidence: 49%
“…Measurements of endogenous EPO production would have been of interest in the present trial to evaluate and compare natural EPO production with the two treatments. Studies in nontransplant subjects with various degrees of renal function have shown that, in subjects with a GFR above 40 ml/min, there is an inverse relationship between EPO and GFR, although those subjects with anemia have higher EPO levels [16,17]. Below a GFR of 40 ml/min, and particularly below 20 ml/min, the EPO response to anemia is muted, probably due to the inability of the damaged kidney to respond adequately to a hypoxic stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney is the major source of erythropoietin (EPO) erythropoietin (EPO) production in the body. Thus, the pathogenesis of anemia in patients with chronic renal failure has been greatly attributed to EPO deficiency (1)(2)(3). With regards to EPO analysis, the most popular clinical method used for determining EPO levels is radioimmunoassay (RIA) (4,5).…”
Section: Introductionmentioning
confidence: 99%